2016
DOI: 10.1002/masy.201500078
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Semicrystalline Syndiotactic Polystyrene with Sulfonated Amorphous Phase, for a Fast and Efficient Removal of VOC Pollutant Traces From Water

Abstract: Summary Syndiotactic polystyrene films and aerogels with nanoporous crystalline phase and sulfonated amorphous phase have been prepared and characterized. The nanoporous nature of the crystalline phase confers to these materials a high solubility of volatile organic compounds (VOCs) from aqueous solutions even at low VOC concentrations while the sulfonation of the amorphous phase enhance the VOC sorption kinetics. These combined properties make these materials particularly interesting for a potential use as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These results can be explained by a continuous decrease in the degree of crystallinity with an increase in the sulfonation degree for s-PS aerogels [ 24 ], while for PPO aerogels, the degree of crystallinity remained substantially constant for the range of sulfonation degree investigated; thus, the uptake capacity of PPO aerogels did not vary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results can be explained by a continuous decrease in the degree of crystallinity with an increase in the sulfonation degree for s-PS aerogels [ 24 ], while for PPO aerogels, the degree of crystallinity remained substantially constant for the range of sulfonation degree investigated; thus, the uptake capacity of PPO aerogels did not vary.…”
Section: Resultsmentioning
confidence: 99%
“…Materials 2022, 15,1947 2 of 11 Sulfonated s-PS monolithic aerogels with a hydrophobic nanoporous-crystalline phase and a hydrophilic sulfonated amorphous phase have been prepared through the sulfonation of s-PS physical gels, followed by the supercritical CO 2 extraction of the solvent [22]. As a result of the high and fast water uptake, these sulfonated s-PS monolithic aerogels present VOC sorption kinetics of up to three orders of magnitude higher than unsulfonated aerogels and five orders of magnitude higher than sulfonated s-PS film [23,24]. However, it has also been observed that, due to sulfonation, the aerogel uptake capacity significantly decreases.…”
Section: Introductionmentioning
confidence: 99%